USING MODERN MICROCONTROLLERS IN AUTOMATED DATA PROCESSING OF SPHYGMIC CARDIOSIGNALS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the concept of developing an automated device for processing pulse signals obtained from several nearby wrist points using the methods of Avicenna and modern alternative medicine. Such devices can be used in home and field conditions and are useful in the early warning of various diseases and giving recommendations for the examination of doctors with relevant specializations.